Perancangan Business Digital Platform dalam Mendukung Keberlanjutan IKM dengan Pendekatan Quality Function Deployment - Debrina Puspita Andriani; Ihwan Hamdala; Suluh Elman Swara; Harry Fadli (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2019)
The development of manufacturing sector with digital platforms is the latest technological advances in industry 4.0 era. The use of e-commerce as business digital platform in marketing activities is very potential to be developed for improving SMEs performance. To build a digital platform that fits with the needs of SMEs and users, Quality Function Deployment (QFD) was conducted to obtain informations in designing a customer-based digital platform. After the customer's needs were obtained, product specifications, concept development and selection, product design testing, industrial design analysis, and prototyping also had been conducted. The analysis showed three highest ranking for digital platform design were an application with specific information product, attractive design of the interface, and adequate security. Furthermore, the function criterias were arranged to formulate alternatives, i.e. how to log in, button shape, color, font size, and database properties. While the screening and assessment criteria were based on ease of transaction, availability of information, and ease of use.